Organic polysilazane / phenolic resin composite micro / nano ceramic material as well as preparation method and application thereof
Through the preparation of organopolysilazane/phenolic resin composite micro/nanoceramic materials, nitrogen-doped carbon materials are used to improve the conductivity and structural stability of SiCNO/C composite materials, and the problems of low conductivity and high volume expansion of SiOx materials are solved, achieving high specific capacity and good cycle stability.
Patent Information
- Application Number
- CN202510042009.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing SiOx materials have low electronic conductivity and high volume expansion, which affects their structural stability and cycling performance.
The SiCNO/C composite material was prepared by the sol-gel method using the organic polysilazane/phenolic resin composite micro/nanoceramic material, and the conductivity and structural stability were improved by nitrogen-doped carbon material.
The high specific capacity and excellent cycle stability of SiCNO/C composites are achieved, which improves electrical conductivity and reduces volume changes.
Smart Images

Figure CN119822853A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic material preparation, in particular to an organic polysilazane / phenolic resin composite micro / nano ceramic material and a preparation method and application thereof. Background Art
[0002] Previous studies have confirmed that SiCNO ceramics generated by organic polysilazane at 1000°C contain amorphous carbon, Si3N4, and a large amount of silicon oxide. x ) is studied as a substitute for Si due to its relatively low volume expansion rate. Compared with Si, SiO x It has the advantages of low cost, easy synthesis, small volume expansion, etc., and can produce inert Li2O and lithium silicate (Li4SiO4, Li2Si2O5) that have a buffering effect on volume expansion during the lithiation process. x Like elemental Si, it faces the problems of high volume expansion rate and low conductivity. Currently, it is difficult to manufacture SiO2 uniformly distributed in carbon materials. x Composite materials composed of carbon materials have been considered as one of the most effective ways to improve these problems. Carbon materials can effectively enhance the conductivity and reduce the x The volume change of the composite material makes it have excellent structural stability and cycle performance.
[0003] In order to solve the SiO x To solve the problem of low electronic conductivity, people have used various conductive materials and SiO x Blended and designed SiO with different morphologies x / carbon composites. Among them, carbon materials are the most studied conductive materials due to their high conductivity and chemical stability. On the other hand, nitrogen-doped carbon materials can change the charge distribution and surface polarity on the surface of the material, thereby greatly improving the charge transfer kinetics of carbon electrode materials. In addition, nitrogen-doped carbon materials can provide pseudocapacitance and additional Li + Storage location. Summary of the invention
[0004] The purpose of the present invention is to provide an organic polysilazane / phenolic resin composite micro / nano ceramic material and a preparation method and application thereof. The prepared SiCNO / C composite material exhibits high specific capacity and excellent cycle stability.
[0005] To achieve the above object, the present invention provides an organic polysilazane / phenolic resin composite micro / nano ceramic material, which has a spherical morphology, wherein the four elements C, N, O, and Si are evenly distributed on the sphere.
[0006] The present invention provides a method for preparing the above-mentioned organic polysilazane / phenolic resin composite micro / nano ceramic material, comprising the following steps:
[0007] Step 1, preparing an organic polysilazane / RF polymer;
[0008] Step 2: Prepare SiCNO / C, i.e., organic polysilazane / phenolic resin composite micro / nano ceramic material.
[0009] Preferably, the specific operation of step one is: mixing ammonia water, deionized water and anhydrous ethanol evenly, then adding resorcinol to fully dissolve, stirring and mixing evenly, adding formaldehyde, adding silazane oligomer after the reaction, continuing the reaction, and after the reaction is completed, placing the obtained product in a centrifuge for centrifugation, and washing with anhydrous ethanol to obtain an organic polysilazane / RF polymer.
[0010] Preferably, the specific operation of step 2 is: vacuum drying the organic polysilazane / RF polymer obtained in step 1, placing the dried polymer in a quartz boat, carbonizing it under a nitrogen atmosphere to obtain a SiCNO / C sample, grinding the obtained SiCNO / C sample, grinding it into powder and then ball milling it to obtain SiCNO / C.
[0011] Preferably, in step 1, the volume ratio of ammonia water, deionized water and anhydrous ethanol is 0.1-0.3:10-30:5-16, the amount of resorcinol is 0.03-1g, the amount of formaldehyde is 0.05-0.15mL, the amount of silazane oligomer is 0.5-1.0mL, and the reaction is carried out for 10-12h.
[0012] Preferably, in step 1, the centrifuge speed is 5000-10000 rpm / min, the centrifugation time is 5-20 min, and the anhydrous ethanol is used for washing 3-5 times.
[0013] Preferably, in step 2, the drying temperature is 50-100°C, the drying time is 18-20h, the carbonization temperature is 800-1000°C, the heating rate is 5-10°C / min, the carbonization time is 3-5h, the grinding speed is 300rpm / min, and the ball milling time is 5-10h.
[0014] The present invention provides an application of an organic polysilazane / phenolic resin composite micro / nano ceramic material, and applies the organic polysilazane / phenolic resin composite micro / nano ceramic material as a negative electrode material for a lithium ion battery.
[0015] Therefore, the present invention adopts the above-mentioned organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application, and the prepared SiCNO / C composite material exhibits high specific capacity and excellent cycle stability.
[0016] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a preparation flow chart of the organic polysilazane / phenolic resin composite micro / nano ceramic material of the present invention and its preparation method and application embodiment;
[0018] Figure 2 The infrared spectra of the organopolysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application examples of the present invention and SiCNO / C are shown;
[0019] Figure 3 The XRD diffraction spectrum of the SiCNO / C composite microspheres of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application example of the present invention and the Raman scattering images of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3;
[0020] Figure 4 The organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application examples of the present invention are scanning electron microscope images of SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3, and a transmission electron microscope image of SiCNO / C-1 and its element distribution map;
[0021] Figure 5 The XPS full spectrum, Si2p high-resolution XPS spectrum, C1s high-resolution XPS spectrum and N1s high-resolution XPS spectrum of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application example of the present invention;
[0022] Figure 6 It is the Si2p high-resolution XPS spectra of SiCNO / C-2 and SiCNO / C-3 of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application examples of the present invention;
[0023] Figure 7 Cyclic voltammetry curves of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application examples of the present invention;
[0024] Figure 8The first cycle capacity-voltage curve of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application example of the present invention, and the current density is 100 mA·g -1 Cyclic performance and Coulombic efficiency of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3, rate performance curves of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3, and the current density of the first three cycles is 100 mA g -1 The subsequent cycle current density is 1A·g -1 Long cycle performance curves of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3;
[0025] Fig. 9 The electrochemical impedance spectra of SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3 of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application examples of the present invention, and the equivalent circuit diagrams of SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3 before and after cycling;
[0026] Fig.10 The SiCNO / C-1 of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application example of the present invention is 0.1-1mV·s -1 CV curve, linear relationship between Log(i) and Log(v), 0.1-1mV·s -1 The contribution of capacitance control to capacity and 0.1mV·s -1 The contribution of pseudocapacitance to the total capacitance.
[0027] Fig.11 The SEM images of the SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3 electrode planes of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application examples of the present invention before and after 100 charge and discharge cycles;
[0028] Fig.12 The SEM images of the corresponding cross sections of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 electrodes of the organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application examples of the present invention before and after 100 charge and discharge cycles;
[0029] Fig.13 The organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application example of the present invention are SiO xFirst charge and discharge voltage curves of SiCNO / C-1 and current density of 100 mA g -1 When SiO x Cycling performance and Coulombic efficiency of SiCNO / C and SiCNO / C-1;
[0030] Fig.14 The organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application example of the present invention are SiO x Electrochemical impedance spectroscopy of SiCNO / C and SiCNO / C-1 before cycling, SiO x / C cycling before and after electrochemical impedance spectroscopy and mapping of SiO at low frequency x Z' vs.ω of SiCNO / C and SiCNO / C-1 impedance -1 / 2 curve;
[0031] Fig.15 The organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application example of the present invention are SiO x SEM images of the Si / C electrode before and after 100 charge-discharge cycles. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0033] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0034] The invention provides an organic polysilazane / phenolic resin composite micro / nano ceramic material, which has a spherical morphology, wherein four elements of C, N, O and Si are evenly distributed on the sphere.
[0035] like Figure 1 As shown, the preparation method of the above-mentioned organic polysilazane / phenolic resin composite micro / nano ceramic material uses The organosilicon / RF polymer composite microspheres were synthesized by the method. Under this condition, the ethoxy groups in the silazane oligomer (OPSZ 1001) were hydrolyzed and condensed. At the same time, resorcinol and formaldehyde condensed to form resorcinol formaldehyde (RF) polymer. Since the reaction rates of the above two reactions are similar, and there is a hydrogen bond interaction between the -Si-OH generated by hydrolysis and the phenolic hydroxyl group of phenol, the silazane oligomer can be co-condensed with resorcinol and formaldehyde to form homogeneous organopolysilazane / RF polymer microspheres. After a carbonization process at 1000°C in a nitrogen environment, nitrogen-doped composite microspheres (SiCNO / C) with uniform distribution of elements are generated, which specifically includes the following steps:
[0036] Step 1: Pass Preparation method for preparing organic polysilazane / RF polymer: mix ammonia water, deionized water and anhydrous ethanol evenly, then add resorcinol to fully dissolve, stir and mix evenly, add formaldehyde, add silazane oligomer after the reaction, continue the reaction, after the reaction is completed, place the obtained product in a centrifuge for centrifugation, and wash with anhydrous ethanol to obtain organic polysilazane / RF polymer (Organpolysilazane / RF, referred to as OPSZ / RF).
[0037] The volume ratio of ammonia water, deionized water and anhydrous ethanol is 0.1-0.3:10-30:5-16, the amount of resorcinol is 0.03-1g, the amount of formaldehyde is 0.05-0.15mL, the amount of silazane oligomer is 0.5-1.0mL, and the reaction is carried out for 10-12h.
[0038] The centrifuge speed is 5000-10000 rpm / min, the centrifugation time is 5-20 min, and the sample is washed with anhydrous ethanol 3-5 times.
[0039] Step 2: Prepare SiCNO / C, i.e., organic polysilazane / phenolic resin composite micro / nano ceramic material: vacuum dry the organic polysilazane / RF polymer obtained in step 1, put the dried polymer into a quartz boat, and carbonize it under a nitrogen atmosphere to obtain a SiCNO / C sample. Grind the obtained SiCNO / C sample, grind it into powder, and then ball mill it to obtain SiCNO / C.
[0040] The drying temperature is 50-100°C, the drying time is 18-20h, the carbonization temperature is 800-1000°C, the heating rate is 5-10°C / min, the carbonization time is 3-5h, the grinding speed is 300rpm / min, and the ball milling time is 5-10h.
[0041] Figure 2 The infrared spectrum of the product obtained in step 1 and step 3 is shown in Figure 1. The infrared spectrum of the sample shows that the organic polysilazane / RF composite microspheres have a wavelength of 3590 cm before carbonization. -1 The absorption peak of -OH appears at 1614 cm-1, and the absorption peak of the carbon-carbon double bond on the benzene ring appears at 1614 cm-1. -1 and 1450cm -1 At 1269cm -1 The characteristic peak at 916cm is attributed to the stretching vibration of -CH3 in organopolysilazane and CO bond in resorcinol. -1 and 2372cm -1The absorption peaks at 1267cm-1 are attributed to the Si-N and Si-H bonds in the organopolysilazane. After the condensed sample was decomposed at 1000℃ in N2 atmosphere, it was not completely decomposed due to the high thermal stability of C-Si and Si-O bonds. -1 ) and -CH2-(2972cm -1 ) characteristic peak disappears, while Si-O (1051cm -1 ) and -Si-C- bonds (817 cm -1 ) appears after pyrolysis.
[0042] The present invention provides an application of an organic polysilazane / phenolic resin composite micro / nano ceramic material, and applies the organic polysilazane / phenolic resin composite micro / nano ceramic material to a negative electrode material of a lithium ion battery.
[0043] Embodiment 1
[0044] The present invention provides a method for preparing an organic polysilazane / phenolic resin composite micro / nano ceramic material, comprising the following steps:
[0045] Step 1: Adoption Preparation of organopolysilazane / RF polymer by method: First, ammonia water (0.1mL, 25wt%) is mixed evenly with deionized water (20mL) and anhydrous ethanol (8mL), and then resorcinol (0.03g) is added to fully dissolve and mix evenly. After stirring for 1h, formaldehyde (0.05mL) is added thereto. After reacting at room temperature for 24h, silazane oligomer (0.6mL) is added and the reaction is continued for 12h. After the reaction is completed, the obtained product is centrifuged in a centrifuge at a speed of 8000rpm / min for 10min, and washed repeatedly with anhydrous ethanol 3 times to obtain Organpolysilazane / RF-1 (OPSZ / RF-1).
[0046] Step 2: Prepare SiCNO / C, i.e., organic polysilazane / phenolic resin composite micro / nano ceramic material: vacuum dry the obtained Organpolysilazane / RF-1 polymer at 80°C for 24 hours, then put the dried polymer into a quartz boat, and carbonize it at 1000°C (5°C / min, insulation for 3 hours) under N2 atmosphere to obtain a SiCNO / C sample. Grind the obtained sample into powder in an agate mortar, and then ball mill (300 rpm / min) for 6 hours to obtain SiCNO / C, recorded as SiCNO / C-1.
[0047] Embodiment 2
[0048] The only difference between this embodiment and embodiment 1 is the preparation method of step 1: ammonia water (0.15mL, 25wt%) is mixed with deionized water (20mL) and anhydrous ethanol (8mL), and then resorcinol (0.05g) is added to fully dissolve and mix evenly. After stirring for 1h, formaldehyde (0.07mL) is added thereto, and after reacting at room temperature for 24h, silazane oligomer (0.6mL) is added and the reaction is continued for 12h. After the reaction is completed, the obtained product is centrifuged in a centrifuge at a speed of 8000rpm / min for 10min, and washed repeatedly with anhydrous ethanol 3 times to obtain Organpolysilazane / RF-2, and the final product is recorded as SiCNO / C-2.
[0049] Embodiment 3
[0050] The only difference between this embodiment and embodiment 1 is the preparation method of step 1: ammonia water (0.3mL, 25wt%) is mixed with deionized water (20mL) and anhydrous ethanol (16mL), and then resorcinol (1g) is added to fully dissolve and mix evenly. After stirring for 1h, formaldehyde (0.14mL) is added thereto, and after reacting at room temperature for 24h, silazane oligomer (0.6mL) is added and the reaction is continued for 12h. After the reaction is completed, the obtained product is centrifuged in a centrifuge at a speed of 8000rpm / min for 10min, and washed with anhydrous ethanol, and repeated 3 times to obtain Organpolysilazane / RF-3, and the final product is recorded as SiCNO / C-3.
[0051] Comparative Example 1
[0052] Preparation of SiO x The specific operation steps of / C composite microspheres are:
[0053] Step 1, preparation of SiO2 / RF microspheres: Mix ammonia water (0.3mL, 25wt%) with deionized water (20mL) and anhydrous ethanol (16mL), then add resorcinol (1g) to fully dissolve and mix evenly. After stirring for 1h, add formaldehyde (0.14mL). After reacting at room temperature for 24h, add TEOS (0.6mL) and continue to react for 12h. Centrifuge using the same steps as in Example 1, and then wash 3 times to obtain SiO2 / RF microspheres.
[0054] Step 2: vacuum dry the SiO2 / RF microspheres obtained in step 1, and put the dried polymer into a quartz boat, and carbonize it under nitrogen atmosphere to obtain SiO2 / RF microspheres. x / C composite microsphere sample, the obtained SiO x The / C composite microsphere samples were ground in an agate mortar and then ball-milled to obtain SiO x / C composite microspheres.
[0055] In order to determine the structures of the three groups of SiCNO / C products, an X-ray diffractometer was used to analyze the three groups of SiCNO / C samples. Figure 3 As shown, Figure 3 (a) is the XRD diffraction spectrum of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3. It can be seen from the figure that broad diffraction peaks appear at around 23° and 43°, indicating that the carbonized samples are amorphous. X-ray diffraction analysis fully proves that the main components of the three groups of materials are SiO x and amorphous carbon. Figure 3 (b) is the Raman scattering image of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3. Raman spectroscopy is used to analyze the existence form of carbon in SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3. Figure 3 As shown in (b), the Raman spectrum is located at 1330cm -1 and 1608cm -1 The peaks are respectively assigned to the D band and G band of the carbon material, proving the presence of amorphous carbon in the product after carbonization of the organic polysilazane / RF polymer.
[0056] Figure 4 (a)-(f) are scanning electron microscope images of three groups of organic polysilazane / RF polymers and SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3. It can be observed from the figure that with the decrease of the content of silazane oligomers, the particle size of the organic polysilazane / RF polymer microspheres gradually increases. The reason is that the change in content during the co-condensation of organic polysilazane and phenolic resin leads to the asynchronous condensation rate. It can also be seen from the figure that the three groups of samples SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3 all have typical spherical morphology. Figure 4 The EDS mapping of SiCNO / C-1 shown in (g) shows that the four elements C, N, O, and Si in the SiCNO / C-1 sample are uniformly distributed in the spherical SiCNO / C-1. This result can be achieved thanks to the fact that during the condensation process of the organosilazane oligomer OPSZ1001 with formaldehyde and resorcinol, the hydrolysis and condensation rates of the silazane oligomer and the phenolic resin are relatively matched.
[0057] Figure 5 The results shown in (a) are consistent with the EDS results. The XPS spectrum shows that the SiCNO / C-1 sample is composed of four elements: C, N, O, and Si, as shown in Table 1. The high-resolution spectrum of silicon after carbonization of OPSZ / RF polymer at 1000°C is shown in Figure 5As shown in (b), the high-resolution Si2p peak is fitted to three peaks at 102.5eV, 103.3eV, and 103.9eV, corresponding to Si 2+ 、Si 3+ and Si 4+ Three valence states. After calculation, Si 2+ 、Si 3+ and Si 4+ The ratio is 6.5:47.3:46.1, and its average valence is determined to be 3.39. Figure 5 (c) in the figure shows that C1s is divided into four peaks at 284.8 eV, 285.8 eV, 286.5 eV, and 288.9 eV, proving the existence of CC / C=C, CN, CO, and C=O bonds in the SiCNO / C-1 composite material. Figure 5 (d) in the figure shows that the N1s spectrum is divided into three peaks, corresponding to pyridinic nitrogen (398.5 eV), pyrrolic nitrogen (400.8 eV) and graphitic nitrogen (400.4 eV), proving that nitrogen doping has been successfully achieved in SiCNO / C. Since nitrogen doping produces more "defects", these "defects" can provide more reactive sites for lithium ion embedding, which is beneficial to improving the ion / electron transport capacity of SiCNO / C-1 materials, thereby improving their electrochemical performance. The Si2p high-resolution spectra of samples SiCNO / C-2 and SiCNO / C-3 are shown in Figure 2. Figure 6 As shown, the average valence states of Si are 3.29 and 3.27, respectively.
[0058] Table 1 Content of elements in SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3
[0059] Sample C (wt%) N (wt%) O(wt%) Si (wt%) SiCNO / C-1 43.3 6.2 28.4 22.1 SiCNO / C-2 46.3 3.9 30.9 18.9 SiCNO / C-3 52.6 2.0 29.6 15.8
[0060] The prepared SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 were used as negative electrode materials for lithium-ion batteries, and the lithium storage performance of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 when used as negative electrode materials was studied by cyclic voltammetry.
[0061] Figure 7 Demonstrated 0.1mV·s -1 Cyclic voltammetry curve of SiCNO / C electrode material. Figure 7 (a) is the cyclic voltammetry curve of SiCNO / C-1. Figure 7 (b) is the cyclic voltammetry curve of SiCNO / C-2. Figure 7 (c) in the figure is the cyclic voltammetry curve of SiCNO / C-3. Figure 7(a) shows that the first cycle CV curve of SiCNO / C-1 has a reduction peak near 0.54V, which no longer appears in subsequent cycles, indicating that the electrolyte decomposition occurred in this cycle and a solid electrolyte membrane (SEI) was formed. In addition, a reduction peak appeared near 1.28V, which is consistent with the Li and SiO x The sharp reduction peak near 0.01 V is due to the formation of Si-Li alloy, and the broad anodic peak in the range of 0.5-1 V is related to the formation of Li x It is related to the dealloying of Si alloy and the formation of amorphous silicon.
[0062] In the subsequent cycles, a new reduction peak appears at 0.27 V due to the alloying of amorphous Si; moreover, the CV curves almost overlap in the following few cycles, which indicates that the SiCNO / C electrode has a low polarization degree during the cycle and the reversibility of the reaction is high. Figure 7 (b) and Figure 7 In (c), it is observed that SiCNO / C-2 and SiCNO / C-3 have similar cyclic voltammetry curves, indicating that SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3 composites have the same electrochemical behavior.
[0063] Figure 8 (a) is the sample current density of 100 mAh g -1 The first cycle capacity-voltage curve of SiCNO / C samples. It can be seen from the figure that the first discharge specific capacity of SiCNO / C-1 is 2094.2 mAh·g -1 and 1309.0mAh·g -1 , the first cycle CE is 62.5%. In contrast, the first discharge specific capacities of SiCNO / C-2 and SiCNO / C-3 are 1133.4 mAh·g -1 and 996.5mAh·g -1 , the first cycle CE of SiCNO / C-2 and SiCNO / C-3 are 65.1% and 61.2% respectively. The reason for the low Coulomb efficiency is that the SEI film is generated during the first cycle of charge and discharge, and the irreversible electrochemical reaction occurs to generate silicate and lithium oxide, which is also reflected in the CV test results. With the increase of carbon content in the sample, the first cycle CE decreases, which is attributed to the fact that the carbon content in the sample enhances the conductivity and structural stability of the sample. Figure 8 (b) shows that SiCNO / C-1 can still maintain 797.6 mAh g after 100 cycles. -1The discharge capacity of SiCNO / C-2 and SiCNO / C-3 electrodes is 541.4 mAh g after 100 cycles of charge and discharge at the same current density. -1 , the discharge capacity of SiCNO / C-3 is only 420.1mAh·g -1 From the above results, it can be seen that the SiCNO / C electrode exhibits a high reversible capacity and excellent cycle stability and coulombic efficiency. The good cycle performance of SiCNO / C is attributed to the SiO x The uniform distribution in nitrogen-doped carbon spheres limits their volume change and improves the electrical conductivity.
[0064] Figure 8 (c) shows the rate performance of the composite materials containing SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3, with a reversible capacity of 1066.1 mAh g in the first cycle. -1 , then in order at 100, 200, 500, 1000, 1500 and 2000mAh·g -1 The rate performance was tested at a current density of 100 mAh g. When the cycle was 31 to 35, the current density returned to 100 mAh g -1 When the reversible capacity of the battery can still be restored to 827.8 mAh g -1 , after high-rate cycling, it can still recover to a relatively high specific capacity, indicating that the sample is structurally stable during lithiation and delithiation, and no serious structural damage occurs. Similar to SiCNO / C-1, the reversible capacity of SiCNO / C-2 and SiCNO / C-3 can also be recovered after cycling at a higher current density, indicating that the spherical SiCNO / C composite material has good structural stability during the rate test.
[0065] Figure 8 (d) shows the long cycle performance of SiCNO / C at 1A·g -1 The SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 electrodes were subjected to 400 discharge / charge cycles at a current density of 1.5 to test the cycle stability of the samples. After activation, SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 showed 893.6 mAh·g -1 、479.5mAh·g -1 and 458.2mAh·g -1Overall, although the capacity decay of SiCNO electrode materials was obvious during the first 40 cycles, the discharge capacity of SiCNO / C-1 was 587.0 mAh g at the 400th cycle. -1 , while the discharge specific capacity of SiCNO / C-2 and SiCNO / C-3 is only 358.2 mAh·g -1 and 257.7mAh·g -1 , indicating that the cycling stability of SiCNO / C-2 and SiCNO / C-3 is relatively poor.
[0066] Fig. 9 (a) shows the electrochemical impedance spectroscopy (EIS) test results of three groups of samples SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3. The larger semicircle diameter in the Nyquist plot represents the charge transfer resistance (Rct), and the smaller semicircle diameter represents the impedance generated by SEI (R S ), and the test results are fitted, as shown in Table 2. Although SiCNO / C-3 has a higher carbon content among the three groups of samples, SiCNO / C-1 has the lowest impedance among the three groups of samples. The reason for this phenomenon is that the carbon content in SiCNO / C-3 is too high, the element distribution is uneven, and the particle size of SiCNO / C-3 is large, which has a poor effect on suppressing volume expansion during the charge and discharge cycle process and will affect the performance of the material capacity. In addition, from Fig. 9 It can be seen from (b)-(d) that since the material is activated during the cycle, the impedance of the three groups of samples becomes lower after the charge and discharge cycle.
[0067] Table 2 EIS impedance fitting results of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 before cycling
[0068] Sample <![CDATA[R s (Oh)]]> <![CDATA[R ct (Oh)]]> SiCNO / C-1 0.5 87.1 SiCNO / C-2 0.8 123.7 SiCNO / C-3 1.8 160.8
[0069] In order to further explore the lithium storage mechanism of SiCNO / C microsphere anode materials, the lithium ion battery was tested at different scan rates (0.1, 0.2, 0.5 and 1.0 mV·s -1 ) to perform CV test on SiCNO / C-1, such as Fig.10 As shown in (a) in the figure. Fig.10 (a) found that 0.1-1.0mV·s -1 The shape of the scanned CV curves is highly consistent, and the relationship between the peak current (i) and the scan rate (v) obeys the functional relationship shown in formula (1):
[0070] i=av b (1);
[0071] Among them, the a value is an adjustable value, and the b value can be obtained from the fitting slope of the Log(v)-Log(i) graph. It is an indicator of charge storage dynamics and can reveal the corresponding electrode storage mechanism. Fig.10 As shown in (b) of Figure 2, for the oxidation / reduction peaks, the calculated b values are 0.64 and 0.77, respectively, which indicates that the total capacity includes both the capacitance process and the diffusion control process. Fig.10 As shown in (c), the response current (i) at a specific scan rate (v) can be quantitatively described as: the pseudocapacitive control process (k1v) and the diffusion control process (k2v 1 / 2 ) is a combination of two different mechanisms, and its expression is shown in formula (2):
[0072] i(v)=k1v+k2v 1 / 2 (2);
[0073] Fig.10 The results of (c) in Figure 3 show that as the scan rate increases, the pseudocapacitive contribution increases, while the diffusion contribution decreases accordingly, indicating that the pseudocapacitive control process has a significant effect on the total capacity of the electrode, especially at higher scan rates. By calculating the k1 and k2 values, the contribution of pseudocapacitance to the battery capacity can be calculated. Fig.10 As shown in (d) in the figure, the -1 During scanning, the pseudocapacitance contribution of the SiCNO / C-1 electrode is about 33.5%. The pseudocapacitance control ratio increases with the increase of scanning rate, which indicates that the capacitance control mechanism contributes to the Li + Fast insertion / extraction at higher scan rates.
[0074] Therefore, SiCNO / C-1 electrode has a -1 The SiCNO / C pseudocapacitor has a high rate capability and stable long-term cycling performance. The reasons for the high contribution of SiCNO / C pseudocapacitor can be explained from the following aspects: (1) The large specific surface area of SiCNO / C microspheres can provide enough reactive sites for the storage of lithium ions; (2) Nitrogen doping in carbon materials creates more "defects" in the materials, which is conducive to the storage of Li + Provides additional storage locations.
[0075] In order to further compare the structural stability of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 composites, the electrode morphology of the materials before and after 100 lithiation / delithiation cycles was observed by scanning electron microscopy. Fig.11 As shown. Fig.11 (a) is the SEM image of the SiCNO / C-1 electrode plane before 100 charge and discharge cycles. Fig.11 (b) is the SEM image of the SiCNO / C-2 electrode plane before 100 charge and discharge cycles. Fig.11 (c) is the SEM image of the SiCNO / C-3 electrode plane before 100 charge and discharge cycles. Fig.11 (d) is the SEM image of the SiCNO / C-1 electrode plane after 100 charge and discharge cycles. Fig.11 (e) is the SEM image of the SiCNO / C-2 electrode plane after 100 charge and discharge cycles. Fig.11 (f) in the figure is a SEM image of the SiCNO / C-3 electrode plane after 100 charge-discharge cycles. As can be seen from the figure, after 100 charge-discharge cycles, due to the formation of SEI film on the surface of the electrode, the surface of the SiCNO / C-1 electrode is relatively smooth and flat, without obvious cracks and powdering, while the surfaces of the SiCNO / C-2 and SiCNO / C-3 electrodes have different degrees of cracking or powdering.
[0076] like Fig.12 As shown, the cross-section of SiCNO / C-1, SiCNO / C-2 and SiCNO / C-3 as electrodes was tested by SEM, and the volume expansion rates of the three groups of samples after cycling were compared. Fig.12 (a) is the SEM image of the corresponding cross section when SiCNO / C-1 is used as an electrode before 100 charge and discharge cycles. Fig.12 (b) is the SEM image of the corresponding cross section when SiCNO / C-2 is used as an electrode before 100 charge and discharge cycles. Fig.12 (c) is the SEM image of the corresponding cross section when SiCNO / C-3 is used as an electrode before 100 charge and discharge cycles. Fig.12 (d) is the SEM image of the corresponding cross section when SiCNO / C-1 is used as an electrode after 100 charge and discharge cycles. Fig.12 (e) is the SEM image of the corresponding cross section when SiCNO / C-2 is used as an electrode after 100 charge and discharge cycles. Fig.12(f) in the figure is the SEM image of the corresponding cross section when SiCNO / C-1 is used as an electrode after 100 charge and discharge cycles. As can be seen from the figure, after 100 cycles, the thickness of the SiCNO / C-1 electrode expands from 19.3μm to 28.5μm, and the volume expansion rate is 47.7%. The volume expansion rates of SiCNO / C-2 and SiCNO / C-3 materials are 37.9% and 50%, respectively. The results show that the volume expansion rates of the three groups of samples SiCNO / C-1, SiCNO / C-2, and SiCNO / C-3 are relatively low, which is attributed to the uniform distribution of nitrogen-doped carbon in the microspheres, which well alleviates the volume change. In addition, the spherical structure has high mechanical stability, and the stress generated by volume expansion will be evenly transmitted to the entire surface of the sphere, thereby reducing the concentration of local stress. This uniform pressure distribution helps to reduce the risk of deformation and rupture of the material, allowing the spherical structure to better withstand volume changes during the cycle. In addition, nitrogen doping will produce larger defects, which can accommodate more Li + , and helps to reduce volume expansion.
[0077] In order to compare the effect of nitrogen doping on the electrochemical properties of the materials, SiO x The charge and discharge performances of SiCNO / C-1 and SiCNO / C-1 were compared. Fig.13 As shown, Fig.13 (a) is SiO x The first charge and discharge voltage curves of SiCNO / C-1 and SiCNO / C-2. Fig.13 (b) is the current density of 100 mA g -1 When SiO x / C and SiCNO / C-1 cycle performance and Coulombic efficiency. As shown in the figure, the first discharge capacity of SiCNO / C-1 is 2094.2mAh·g -1 , the initial CE is 62.5%, while SiO x / C The first discharge capacity is 1244.1mAh·g -1 , and the coulombic efficiency is 58.7%. After 100 charge and discharge cycles, SiCNO / C-1 has a capacity of 797.6 mAh·g -1 The reversible capacity of SiO x / C capacity decays quickly, with 424.1 mAh·g after 100 cycles. -1 The discharge specific capacity of SiCNO / C-1 is significantly improved due to the nitrogen doping, which improves the ion / electron transmission rate.
[0078] Fig.14 (a) and Fig.14 (b) shows the untreated SiO xEIS test results of / C and SiCNO / C before and after cycling, and the test results were fitted to estimate R ct The above data were used to plot the SiO x Z' vs.ω of SiCNO / C and SiCNO / C-1 impedance -1 / 2 Curves, such as Fig.14 As shown in (c) in Table 3 and Fig.14 In (c), it can be seen that SiCNO / C has the lowest charge transfer impedance, indicating that nitrogen doping plays a very important role in the conductivity of the composite material. In addition, after 100 charge and discharge cycles, SiO x / C’s charge transfer impedance (R ct ) is the largest, indicating that nitrogen doping can further enhance the charge transfer kinetics of the material.
[0079] Table 3 SiCNO / C-1 and SiO x EIS impedance fitting results before / C cycle
[0080] Samples Rs(Ω) Rct(Ω) SiCNO / C-1 0.5 67.2 <![CDATA[SiO x / C]]> 0.7 179.6
[0081] In order to intuitively show the effect of nitrogen doping on the conductivity of the material, the lithium ion diffusion coefficient of the above SiCNO / C-1 is calculated according to formula (3):
[0082]
[0083] Calculated SiO x / D of C and SiCNO / C-1 composites Li+ The values are 1.07×10 -15 cm 2 ·s -1 4.23×10 -15 cm 2 ·s -1 , D Li+ The increase in the value indicates that the insertion and extraction rates of lithium ions in SiCNO / C-1 are faster than those in the other two samples, proving that the introduction of nitrogen improves the electrical conductivity of the carbon composite material.
[0084] To further compare SiO x The structural stability of SiCNO / C and SiCNO / C-1 composites was investigated by scanning electron microscopy after 100 lithiation / delithiation cycles. Fig.15 As shown, Fig.15 (a) is SiO x SEM image of / C electrode before charge and discharge cycle, Fig.15 (b) is SiO xSEM image of the SiCNO / C-1 electrode after 100 charge-discharge cycles. As can be seen from the figure, after 100 charge-discharge cycles, due to the formation of SEI film on the surface of the electrode, the surface of the SiCNO / C-1 electrode is intact without obvious cracks and powdering, while the surface of the SiO x / C electrode surface showed different degrees of cracking or powdering. x / C has the largest cracks on its surface, and after 100 charge and discharge cycles, SiO x / C falls off from the current collector, indicating that the single composite with carbon material is not particularly ideal for inhibiting structural changes. There are almost no cracks on the surface of the nitrogen-doped carbon composite electrode material, proving that nitrogen-doped carbon composite materials play a more important role in limiting volume expansion. Although nitrogen doping does not limit the volume change of the negative electrode material during the cycle, the D Li+ This indicates that nitrogen doping can allow more lithium ions to be embedded into the electrode material in the same amount of time, resulting in a more uniform volume expansion.
[0085] The present invention uses silazane oligomer, resorcinol and formaldehyde as precursors, and utilizes The sol-gel method was used to make the organopolysilazane oligomer (OPSZ 1001) and resorcinol formaldehyde resin (RF) co-hydrolyze and condense to prepare uniformly sized OPSZ / RF composite microspheres, and nitrogen-doped SiCNO / C composite materials were obtained after high-temperature ceramicization. This method is easy to prepare SiCNO / C composite materials with adjustable size (200-1000nm) and controllable carbon content (20-60wt%), and composite microspheres with C, Si, N and O elements uniformly distributed in the SiCNO / C composite materials, and they were used as negative electrode materials for lithium-ion batteries to study their lithiation / delithiation mechanisms. Nitrogen doping in SiCNO / C composite materials provides additional interfacial lithium storage active sites and improves the lithium ion diffusion rate. SiCNO / C composite microspheres exhibit two lithium storage mechanisms: diffusion control and capacitance control. In addition, the spherical structure of SiCNO / C composite microspheres also improves the structural stability of the composite material. Thanks to the above advantages, SiCNO / C composite microspheres, especially SiCNO / C-1, exhibit excellent rate performance and the ability to cycle stably for a long time at high current density. -1 SiCNO / C-1 retains 587.0 mAh g after 400 cycles at the current density -1 The discharge specific capacity and capacity retention rate are 67.5%.
[0086] In addition, SiO x / C composite microspheres, SiO xThe charge and discharge performance of SiCNO / C-1 and SiCNO / C-1 microspheres were compared. The results showed that SiCNO / C-1 composite microspheres had the best electrochemical performance. After 100 charge and discharge cycles, SiCNO / C-1 had a charge and discharge performance of 794.1 mAh g -1 The reversible capacity of SiCNO / C-1 is significantly improved due to the nitrogen doping, indicating that nitrogen doping has an important influence on the improvement of lithium storage performance. x After 100 charge-discharge cycles, the specific capacity of the C / C composite microspheres decayed to only 424.1 mAh·g -1 , indicating that nitrogen doping can further improve the lithium storage performance of the material. The cyclic impedance test of the above three materials shows that SiCNO / C-1 has good structural stability, and nitrogen doping improves the charge transfer kinetics of the composite material, making it have a higher lithium ion migration number, reaching 4.23×10 -15 cm 2 ·s -1 .
[0087] Therefore, the present invention adopts the above-mentioned organic polysilazane / phenolic resin composite micro / nano ceramic material and its preparation method and application, and utilizes (Sol-gel) method, in which organosilazane oligomer (OPSZ) and resorcinol formaldehyde resin are co-condensed to prepare organopolysilazane / phenolic resin (OPSZ / RF) microspheres with uniform size. During the reaction, silanol (-Si-OH) easily interacts with phenol hydroxyl groups through hydrogen bonds, allowing the two to co-condense to form uniform OPSZ / RF polymers, which are then carbonized at high temperature to obtain SiCNO / C composite microspheres. This method is easy to prepare SiCNO / C composite materials with adjustable size (200-1000nm) and controllable carbon content (20-60wt%), and various elements are evenly distributed in the composite microspheres. The prepared SiCNO / C composite materials exhibit high specific capacity and excellent cycle stability.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. Organic polysilazane / phenolic resin composite micro / nano ceramic material, characterized by: The material has a spherical morphology, in which the four elements C, N, O and Si are evenly distributed on the sphere.
2. The method for preparing the organic polysilazane / phenolic resin composite micro / nano ceramic material according to claim 1, characterized in that: The following steps are involved: Step 1, preparing an organic polysilazane / RF polymer; Step 2: Prepare SiCNO / C, i.e., organic polysilazane / phenolic resin composite micro / nano ceramic material.
3. The method for preparing the organic polysilazane / phenolic resin composite micro / nano ceramic material according to claim 2, characterized in that: The specific operation of step one is: mix ammonia water, deionized water and anhydrous ethanol evenly, then add resorcinol to fully dissolve, stir and mix evenly and add formaldehyde, add silazane oligomer after the reaction, continue the reaction, after the reaction is completed, centrifuge the obtained product, and wash it with anhydrous ethanol to obtain an organic polysilazane / RF polymer.
4. The method for preparing the organic polysilazane / phenolic resin composite micro / nano ceramic material according to claim 2, characterized in that: The specific operation of step 2 is: vacuum drying the organic polysilazane / RF polymer obtained in step 1, placing the dried polymer in a quartz boat, carbonizing it under a nitrogen atmosphere to obtain a SiCNO / C sample, grinding the obtained SiCNO / C sample, grinding it into powder, and then ball milling to obtain SiCNO / C.
5. The method for preparing the organic polysilazane / phenolic resin composite micro / nano ceramic material according to claim 3, characterized in that: In step 1, the volume ratio of ammonia water, deionized water and anhydrous ethanol is 0.1-0.3:10-30:5-16, the amount of resorcinol is 0.03-1g, the amount of formaldehyde is 0.05-0.15mL, the amount of silazane oligomer is 0.5-1.0mL, and the reaction is carried out for 10-12h.
6. The method for preparing the organic polysilazane / phenolic resin composite micro / nano ceramic material according to claim 3, characterized in that: In step 1, the centrifuge speed is 5000-10000 rpm / min, the centrifugation time is 5-20 min, and the sample is washed with anhydrous ethanol 3-5 times.
7. The method for preparing the organic polysilazane / phenolic resin composite micro / nano ceramic material according to claim 4, characterized in that: In step 2, the drying temperature is 50-100°C, the drying time is 18-20h, the carbonization temperature is 800-1000°C, the heating rate is 5-10°C / min, the carbonization time is 3-5h, the grinding speed is 300rpm / min, and the ball milling time is 5-10h.
8. Application of organic polysilazane / phenolic resin composite micro / nano ceramic materials, characterized by: The organic polysilazane / phenolic resin composite micro / nano ceramic material according to claim 1 is applied to negative electrode materials of lithium-ion batteries.
Citation Information
Patent Citations
Composite negative material for lithium ion battery and manufacture method of composite negative material
CN104659341A
Macroscopic quantity preparation method of monodispersed SiOx-C composite microspheres
CN107093711A
Method for preparing polysilazane nano-microspheres by using Stber method
CN116284802A
Phenolic resin skeleton carbon layer coated nano silicon composite material and preparation method and application thereof
CN116914127A